Estimation of Stature from External Ear Morphometry: A Preliminary Study - Phad, Laxman G; Bardale, Rajesh V; Haridas, Sandeep V (Journal of Indian Academy of Forensic Medicine, 2023)
External ear is a defining feature of the face that gives a decent and definite look to a human face with an aesthetically fine appearance. Along with hearing, they are one of the most important body parts helping in human identification. The cross-sectional study was undertaken on a total of 149 dead bodies brought for postmortem examination from May 2019 to December 2019 of which 93 were males of age between 18 to 82 years and 56 were females of age between 19 years to 92 years. Total four parameters of the right and left ear that is length (EL), Ear breadth (EB), Ear lobule length (ELL), and Ear lobule breadth (ELB) of the adult population were studied with a digital vernier caliper capable of measuring nearest 0.01 mm and was correlated statistically with body length. In the right ear, the correlation coefficient (r-value) was higher in males for ear length, ear lobule length and lower in right ear lobule breadth, however in the left ear it was higher in females for ear length and ear lobule breadth, but it was higher in males in case of left ear lobule breadth. In the right ear the determination coefficient (r 2 value) was higher in males for ear length, and ear lobule length, and it was higher in females for ear breadth and ear lobule breadth, however in the left ear it was higher in females for ear length, ear breadth but it was higher in male for ear lobule length and ear lobule breadth.